Perancangan Prototipe Konseptual Rekam Medis Elektronik Berbasis Mobile untuk Kedaruratan Bencana di Rumah Sakit Sumber Waras - Diana Barsasella; Nanda Aulia Salsabila; Ari Sukawan (STIKes Persada Husada Indonesia, 2026)
Research Objective: This study aimed to identify disaster-emergency documentation requirements and develop a conceptual mobile electronic medical record prototype for Sumber Waras Hospital, Cirebon. Methodology: An exploratory qualitative case study was conducted using one purposively selected key informant, the Head of the Medical Record Unit. Data were collected through an in-depth interview, direct observation, and document review. Method triangulation was applied by comparing findings across the three data-collection methods. Data were analyzed using the Miles and Huberman interactive model, translated into functional and non-functional requirements, and developed into a high-fidelity Figma prototype using a design thinking approach. Results: The analysis identified requirements for disaster-specific registration, rapid triage documentation, temporary identification of unidentified patients, simplified emergency clinical recording, offline data capture, role-based access control, reporting, and proposed synchronization with the hospital information system. These requirements were represented in the conceptual E-Merge prototype, which includes login, dashboard, disaster-patient registration, emergency documentation, patient search, reporting, and disaster-map modules. Technical implementation, interoperability testing, and multidisciplinary usability evaluation were not conducted. Conclusion: E-Merge provides a preliminary conceptual design for disaster-specific mobile medical record documentation. Its usability, security, offline synchronization, and interoperability with the hospital information system and SATUSEHAT require further multidisciplinary testing before implementation.